Studies on Fern of Lesser Sunda Islands I: Checklist of the Genus Adiantum (Pteridaceae) - Lestari, Wenni Setyo; Adjie, Bayu (Jurnal Biodjati, 2020)
Adiantum or maidenhair fern is one of the largest genera in Pteridaceae. We survey their species diversity in Lesser Sunda Islands, Indonesia through the living collection and herbarium examination. Seventeen species of Adiantum were recorded. including five species that considered as introduced and naturalized species. One species that grows naturally, Adiantum silvaticum, were previously known as endemic to Australia. However, this study revealed the new distribution of this species on Sumba and Flores.